Road Transport Fuel Price and Food Security in the South-East Nigeria - Udemgba, Nelson Obinna; Okoronkwo, Scholastica; Olejeme, Blessing Chiamaka; Ugwu, Nnamdi Simeon; Ogba, Michael Chinonso (Kashere Journal of Politics and International Relations, 2023)
The price of road transport fuel in Nigeria has very significant impact on transportation systems, business operations, and even production processes, including agricultural production. This study explored the impact of fluctuations in price of road transport fuel on food security in the South-east Nigeria. The study adopted a mixed method of data collection as it relied on documented evidences from secondary sources and information gotten from food products marketers, through interviews. Thematic analysis was adopted as the method of data analysis. The Rent-seeking Theory was employed as the theoretical framework of analysis. Findings from the study indicated that the regulation of fuel pump price by the government, manifested in the constant increase in fuel pump price, has undermined the availability of food products in South-east Nigeria. The study also found that industrial actions carried out by fuel suppliers in response to unfavorable government policies, negatively affects food affordability in the Southeast Nigeria. The study made recommendations for policy implementation by the federal government and state governments in South-east geo-political zone of Nigeria, to cushion the effect of increase in fuel price and constant strikes by petroleum distributors, in a bid to enhance food security in South-East Nigeria.